Influence of gold nanoclusters biomaterials combined with upper limb rehabilitation robot on patients with limb ischemic injury. (4th February 2023) - Zhai, Yan; Guo, Xiaobo; Zhang, Yong; He, Yongzheng; Li, Zhiqiang
The reverse microemulsion was prepared and gold nanoparticles (AuNPs) were synthesised from it. Then, AuNC biomaterials were prepared by modifying folic acid with dendrimers, which were applied to patients with limb ischemic injury. The results showed that the spectra of AuNC synthesised by the two methods of water phase and oil phase were similar, and the spectra of AuNC synthesised before and after folic acid modification were also quite similar. The shoulder adduction scores (55.87 ± 4.07, 69.84 ± 3.87) and shoulder abduction scores (65.38 ± 5.21, 80.21 ± 4.13) of the experimental group after rehabilitation intervention for three and five weeks were significantly high, and those of control group was significantly higher than the blank group (P < 0.05). The arm supination score (40.2 ± 2.48) of the experimental group after rehabilitation intervention was significantly higher than that of the control group (31.44 ± 2.59) and the blank group (29.78 ± 2.76), and that of control group was significantly higher than the blank group (P < 0.05).